Laser system for rydberg gates based on tapered amplifier driven frequency doubler. - Oon, Fong En. (2011)
In this thesis project, effort is concentrated on realizing a 480nm laser system which allows one to excite atoms into Rydberg states with principal quantum number n>>1 for quantum information processing experiment. A 960nm interference-stabilized external-cavity diode laser (ECDL) has been realized. The output power of this laser is amplified by a tapered amplifier to more than 1W. The output of this 960nm laser system is then resonate in a bow-tie cavity resonator to enhance the fundamental beam circulating in the nonlinear crystal to convert the 960nm light to 480nm light.